The graveyard book - Russell, P. Craig (Harper, 2014)
Both volumes of the New York Times bestselling The Graveyard Book Graphic Novel are now available in a single-volume paperback edition. Each chapter in this adaptation by P. Craig Russell now combined into one splendid volume is illustrated by a different luminary from the comic book world, showcasing a variety of styles from a breadth of talent. Together, they bring Neil Gaiman's Newbery Medal-winning, nationally bestselling novel The Graveyard Book to new life in this gorgeously illustrated graphic novel adaptation.